O corpo comunial de Juliano Pessanha: espectros de uma instabilidade perpétua - Yasmin Franca Merelim Magalhaes (2017)
This critical analysis, inaugural, presents the writing of Juliano Garcia Pessanha, that is motivated by an ethical-ontological disposition, that tells and leads to the awakening of a elemental or primordial sensitivity and proposes an originary affection engendered by/in the literary and discoursive devices that take shape within the work, opening thus thecommunality (or communal potency) of the writing, in which are articulated the subjective contents of the links between writing and reading (thrown into the text by allusive and intertextual resources, potential or actual, reactivated by each specific reading). The scripture thus has the value and function of proposing a different health and a different understanding of the status of reality and of human existence, placing language at the center of motivations and ontological justifications, operating a linguistic turn, enabling the inscription of a Himself and of a body of his own, as an outcome of communalarticulations.